The Relationship Of Physical Activity With Cognitive Function In The Elderly In Ciamis Village - Jajuk Kusumawaty; Asep Gunawan; Devina Sutandi (Asy-Syifa : Journal of Science and Technology Nursing, 2023)
Purpose: This study aims to find out about Ciamis Village. Method: This study uses correlational analytical methods with a cross-sectional approach. The sample in this study totaled 99 respondents. Samples were taken using technique sampling quotas and data collection using Mini-Mental State Examination (MMSE) questionnaires and the International Physical Activity Questionnaire Short Form (IPAQ-SF). Data analysis was performed with a chi-square test. The study was conducted in March–April 2022. Results: Based on the results of the study out of 99 respondents there were 48 elderly (98.0%) with less activity experiencing cognitive decline, 1 elderly (2.0%) with less activity having a normal cognitive function, there were 44 elderly (88.0%) with good physical activity having a normal cognitive function, and 6 elderly (12.0%) with good physical activity experiencing a decrease in cognition is a live function. From the results of the chi-square test, it shows that there is a relationship between physical activity and the cognitive function of the elderly in Ciamis Village. Conclusion: Based on the results of this study it was found that better physical activity performed by the elderly results in normal cognitive function or maintenance of cognitive function, conversely if less physical activity results in a decrease in cognitive function.